A focus on CKD reporting and inappropriate prescribing among older patients discharged from geriatric and nephrology units throughout Italy: A nationwide multicenter retrospective cross-sectional study - Aucella, Filippo; Corsonello, Andrea; Soraci, Luca; Fabbietti, Paolo; Prencipe, Michele Antonio; Gatta, Giuseppe; Lattanzio, Fabrizia; Cortese, Livio; Pagnotta, Maria Rosaria; Antonelli Incalzi, Raffaele; Aucella, Filippo; Benevento, Roberta; et al. (Frontiers in Pharmacology, 2022)
Older hospitalized patients with chronic kidney disease (CKD) are a segment of the geriatric population with a substantial risk of potentially inappropriate medication (PIM) use; the high rates of multimorbidity and polypharmacy, along with the progressive decline of eGFR, contribute to increase the risk of drug-drug and drug-disease interactions, overdosing, and adverse drug reactions (ADRs). In this multicenter cross-sectional study, we aimed at evaluating the prevalence of CKD under-reporting and PIMs among older patients discharged from acute geriatric and nephrology units throughout Italy. Renal function was determined by estimating glomerular filtration rate (eGFR) through Berlin Initiative Study (BIS) equation; prevalence of PIMs was calculated by revising drug prescriptions at discharge according to STOPP criteria, Beers criteria, and summaries of product characteristics (smPCs). A descriptive analysis was performed to compare clinical and pharmacological characteristics of patients in the two distinct settings; univariate and multivariate logistic regression models were performed to explore factors associated with CKD under-reporting in the discharge report forms and PIMs prevalence. Overall, the study population consisted of 2,057 patients, aged 83 (77-89) years, more commonly women, with a median 7 (5-10) drugs prescribed at discharge. CKD under-reporting was present in 50.8 % of the study population, with higher rates in Geriatric vs Nephrology Units (71.1 vs 10.2 %, p<0.001). 18.5 % of the study population was discharged with at least one renally inappropriate medication; factors associated with at least one contraindicated drug at discharge were number of drugs (PR 1.09, 95%CI 1.14-1.19), atrial fibrillation (PR 1.35, 95%CI 1.01-1.81), diabetes (PR 1.61, 95%CI 1.21-2.13), being hospitalized in Nephrology Units (PR 1.62, 95%CI 1.14-2.31), CKD stage 3b (PR 2.35, 95%CI 1.34-4.13), and stage 4-5 (PR 14.01, 95%CI 7.36-26.72). Conversely, CKD under-reporting was not associated with the outcome. In summary, CKD under-reporting and inappropriate medication use was common in older patients discharged from hospital; the relatively high number of PIMs in both nephrology and geriatric settings underline the need to improve appropriate prescribing during hospital stay, to decrease the risk of ADRs and side effects in this highly vulnerable population.